PELATIHAN MANAJEMEN KEUANGAN KELUARGA : SEKOLAH PRA NIKAH BRIGHT SCHOLARSHIP - YBM BRILiAN - Solovida, Grace Tianna (Fokus ABDIMAS, 2023)
The importance of family financial management in the sustainability of a family's life is essential. Couples planning to get married in the future need to understand the importance of family financial management from the beginning to plan their finances well and prevent future financial problems. Lack of understanding of financial management can also cause difficulties in managing their finances.. Therefore, it is important for couples to understand family financial planning and prepare themselves financially before marriage to manage their finances well and prevent serious financial problems in the future. The purpose of pre-marital counseling with family financial planning material is to provide knowledge and skills in managing family finances to couples who will get married. This activity aims to equip them with the necessary knowledge to manage family finances effectively and efficiently. Specific objectives of this pre-marital counseling include giving an understanding of the importance of family financial planning, explaining basic concepts and principles of family financial planning, providing real-life examples and simulations to apply financial planning principles in daily life, and increasing financial literacy and responsibility. The pre-marital counseling was held by Bright Scholarship Yayasan Baitul Maal BRILiAN Regional Office Semarang.Keywords: pre-marital counseling, family financial planning